çŽ°ä»£æ±‰è¯çš„â€œéš¾é“â€å’Œå°å°¼è¯çš„â€œMemangâ€å¯¹æ¯”ç ”ç©¶ - David Vincensius (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2023)
æ‘˜è¦Â åé—®å¥æ˜¯çŽ°ä»£æ±‰è¯çš„å¥åç±»åž‹ä¹‹ä¸€ã€‚åé—®å¥ä½¿æˆ‘ä»¬åœ¨æ—¥å¸¸ç”Ÿæ´»å½“ä¸çš„äº¤æµæ›´åŠ ä¸°å¯Œã€‚é™¤äº†ä¸æ–‡ä¹‹å¤–ï¼Œå°å°¼è¯ä¹Ÿæœ‰åé—®å¥ã€‚çŽ°ä»£æ±‰è¯åé—®å¥çš„ç‰¹ç‚¹ä¹‹ä¸€æ˜¯åœ¨å‰è¾¹çš„éƒ¨åˆ†æœ‰â€œéš¾é“â€ä¸€è¯ï¼Œä¸è¿‡å°å°¼è¯æ²¡æœ‰ä»€ä¹ˆæ ‡å‡†çš„åé—®è¯è¯ã€‚è™½ç„¶è¿™æ ·ï¼Œä½†æ˜¯å°å°¼äººåœ¨æ—¥å¸¸ç”Ÿæ´»å½“ä¸å¸¸æŠŠâ€œMemangâ€è¯ç”¨åœ¨åé—®å¥åã€‚è¿™é¡¹ç ”ç©¶çš„ç›®çš„æ˜¯å¯¹æ¯”è¯è¨€ç ”ç©¶ï¼Œæ—¢è¯´æ˜ŽçŽ°ä»£æ±‰è¯çš„â€œéš¾é“â€ä¸Žå°å°¼è¯çš„â€œMemangâ€å¯¹æ¯”ã€‚æ‹¿è¯å…¸å’Œå…¶å®ƒæ–‡ç« æ¥åšè¯å…¸å¦å’Œæ–‡çŒ®ç ”ç©¶ï¼Œç»“æžœè¡¨æ˜Žï¼Œå°å°¼è¯â€œMemangâ€çš„ç”¨æ³•æ¯”è¾ƒä¸°å¯Œã€‚å¦‚æžœæŠŠå°å°¼è¯â€œMemangâ€ç¿»è¯‘æˆä¸æ–‡ï¼Œæˆ‘ä»¬æ‰¾å¾—åˆ°å„ç§å„æ ·çš„è¯è¯ä½œä¸ºå¯¹åº”ã€‚å’Œå°å°¼è¯çš„â€œMemangâ€ç›¸æ¯”ï¼ŒçŽ°ä»£æ±‰è¯â€œéš¾é“â€å”¯ä¸€ä½œç”¨äºŽåé—®å¥ï¼Œç”¨æ³•æ¯”è¾ƒå•ä¸€ã€‚.Â é”®è¯: å¯¹æ¯”ï¼›çŽ°ä»£æ±‰è¯ï¼›éš¾é“ï¼›å°å°¼è¯ï¼›Memang.Â ABSTRACTÂ Rhetorical questions are one of the sentence types in modern Chinese. Rhetorical questions enrich our daily life communication. In addition to Chinese, Indonesian also has rhetorical questions. One of the characteristics of modern Chinese rhetorical questions is the word "éš¾é“" in the front part, but there is no standard rhetorical question in Indonesian. Even so, Indonesians often use the word "Memang" in rhetorical sentences in their daily life. The purpose of this comparative language study is to illustrate the contrast between "éš¾é“" in modern Chinese and "Memang" in Indonesian. Using dictionaries and other articles for lexicography and literature research, the results show that the Indonesian "Memang" has a relatively rich usage. If we translate the Indonesian "Memang" into Chinese, we can find a variety of words to correspond to. Compared with "Memang" in Indonesian, "éš¾é“" in modern Chinese is only used in rhetorical questions, and its usage is relatively simple.Â Â Key Words: Comparative; Modern Chinese; éš¾é“; Indonesian; Memang.Â Â